2012
DOI: 10.1007/978-1-4471-4600-1_79
|View full text |Cite
|
Sign up to set email alerts
|

Reason and Trends for Using Packaged Milk in Pakistan: Study of Urban Pakistani Consumers

Abstract: Milk is one of the basic commodities and important in one's day-to-day life. Pakistan with current estimates is the 4th largest milk producing countries in the world with 33 billion annual productions. Out of the total milk produced, 97% is in the informal sector like loose milk which is then sold in both rural and urban markets. On the contrary, 3% of the total milk produced is catered by packaged milk producing companies and dominated by leading packaged milk brands like, Nestle MilkPak and Olpers by Engro F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Although some reports are available for the determination of OT from Indian subcontinent, there are still no studies from Pakistan. However, Pakistan is the 4th largest milk‐producing country about 33 billion litres annually (Kamran & Rizvi Muhammad Ahsan, ). Yet, milk is one of the main sources of essential nutrients that are consumed by the population of all age groups, because it contains the protein, fat, carbohydrates, vitamins and minerals that are required for growth and maintenance of tissues (Faraz et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some reports are available for the determination of OT from Indian subcontinent, there are still no studies from Pakistan. However, Pakistan is the 4th largest milk‐producing country about 33 billion litres annually (Kamran & Rizvi Muhammad Ahsan, ). Yet, milk is one of the main sources of essential nutrients that are consumed by the population of all age groups, because it contains the protein, fat, carbohydrates, vitamins and minerals that are required for growth and maintenance of tissues (Faraz et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…The milk production increased by 3.2% and meat 4.5% during 2013–14 (Finance, –2014; Qudus et al ., ). In Pakistani population, mostly raw milk is consumed, and only 3% of the total milk production is processed in the dairy industries (Kamran & Rizvi Muhammad Ahsan, ). Only few studies have been reported on the effect of exogenous OT interaction among calf suckling and consequence of OT injections on mineral (potassium, sodium, chloride, calcium and phosphorus) composition of buffalo's milk (Muhammad Subhan & Nazir, ; Aneela et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the basic commodities and a significant part of it is converted to dairy products. Pakistan ranks 4th in milk‐producing countries with approximately 33 billion liters annual production (Kamran and Rizvi ).…”
Section: Mycotoxin Contamination Of Food and Feed In Pakistanmentioning
confidence: 99%
“… 4 However, while melamine concentration is higher than the safety limit [2.5 ppm of United States Food and Drug Administration (US FDA) and 1.0 ppm of infant formula in China], 5 an insoluble compound with cyanuric acid that induces kidney stones could be formed, leading to renal failure and even death in humans. 6 , 7 For example, serious renal failure and deaths of infants have been reported due to the addition of melamine into infant formula in 2008. 8 The serious detrimental consequences of melamine contamination can pose to public health.…”
Section: Introductionmentioning
confidence: 99%